Effects of Maqasid al-Shariah for ethical decision making among social entrepreneurs - Mhd. Sarif, Suhaimi; Ismail, Yusof; Azan, Zaliza (The World Academy of Islamic Management, 2017)
An ethical decision manifests the protection and preservation of benefits and rights of business stakeholders. The mainstream practice is based on conventional ethical principles. The application of Maqasid al-Shariah is limited to Shariah compliant enterprises due to the industrial requirements or the need to gain competitive advantage. The unique model of social enterprises combined for-profit and not-for-profit objectives. Such combination requires balancing between profit and social ends. The application of Maqasid al-Shariah is essential for ethical decision making. The study aims to explore the effects of Maqasid alShariah for ethical decision making among social entrepreneurs. The study covers important aspects of social enterprises, the use of guidelines, measurement on each decision, and wellbeing of stakeholders. Based on personal interview with social entrepreneurs, the application of Maqasid al-Shariah allows for the enhancement of wellness, welfare, and well-being of social enterprises and the key stakeholders. The results of the study suggest there is intermediate impact in terms of triple bottom line and stakeholders’ approach to ethical decision making of social entrepreneurs. The study suggests the use of case study method for future research.